Functionalization of graphene nanostructures with inorganic nanoparticles and their use for the removal of pharmaceutical pollutants in water - Oliveras, Jana; Marcon, Lionel; Bastús, Neus G.; Puntes, Victor (Frontiers in Chemical Engineering, 2022)
A graphene-based hybrid material decorated with Fe3O4 and TiO2 nanoparticles (NPs) to effectively remove emerging pollutants as non-steroidal anti-inflammatory drugs (NSAIDs) Ibuprofen and Diclofenac present in water at low environmental concentrations has been prepared by a one-step functionalization process following a novel gentle and scalable surfactant-depletion approach. Following this method, NPs are progressively deprived of their original surfactant in the presence of graphene, leading to the formation of hybrid nanostructures composed of two different types of NPs well dispersed over the graphene nanosheets. The as-prepared hybrid material possesses high adsorption capacity, superparamagnetic properties, photocatalytic behaviour, and good water dispersibility. Ibuprofen and Diclofenac adsorption kinetics on the composites was investigated via UV-Vis spectroscopy. Thanks to incorporating TiO2 NPs as in situ catalysts, the adsorption performance of composites is restored after use, which could be a promising recycling pathway for the adsorbents in wastewater treatments.